Halal Awareness dalam Membeli Produk Kosmetik di Kalangan Generasi Z - Suwanda; Hikmah, Nur; Yani; Azhwa, Nadya (Al-fiqh, 2025)
Halal cosmetics have become one of the products attracting the attention of modern consumers due to their halal certification and safety in use. This study specifically examines the factors influencing halal awareness on the purchase intention of halal cosmetics among Generation Z students at the Faculty of Economics and Business, Universitas Tanjungpura. Data were collected through questionnaires from 45 respondents and analyzed using descriptive statistics. The majority of respondents were female (86.67%) aged 17–23 years. The results show that 85% of respondents paid close attention to halal labels, 80% preferred certified halal products, and 90% felt safer using halal products. Moreover, 75% were willing to purchase halal products even if they were not yet popular, and 70% were willing to buy them despite relatively high prices. These findings confirm that higher halal awareness increases the purchase intention of students toward halal cosmetic products, providing guidance for producers to develop marketing strategies emphasizing halal certification and product safety to attract young consumers.